Peran Media Sosial Dalam Membangun Dakwah Islam yang Efektif - Ahmad Faza Fauzan Saragih; Rony Fernando Sagala; Erwan Effendi (STIT Sirojul Falah Bogor, 2022)
Along with the times and technology, the way of preaching has also changed. Compared to preaching through speech, currently preaching through writing is more urgent and effective to do, namely preaching using social media such as the internet and writings on social media that contain da'wah messages. The advantages of preaching with this model do not make the preaching material disappear even though the preacher, or the writer has died, as the expression of His Majesty Rasulullah SAW,